Diagnosis and treatment of resistant hypertension - Waeber, Bernard; Volpe, Massimo; Ruilope, Luis M.; Schmieder, Roland (Blood Pressure, 2014)
Abstract Hypertension resistant to lifestyle interventions and antihypertensive medications is a common problem encountered by physicians in everyday practice. It is most often defined as a blood pressure remaining >= 140/90 mmHg despite the regular intake of at least three drugs lowering blood pressure by different mechanisms, one of them being a diuretic. It now appears justified to include, unless contraindicated or not tolerated, a blocker of the renin-angiotensin system and a calcium channel blocker in this drug regimen, not only to gain antihypertensive efficacy, but also to prevent or regress target organ damage and delay the development of cardiorenal complications. A non-negligible fraction of treatment-resistant hypertension have normal "out of office" blood pressures. Ambulatory blood pressure monitoring and/or home blood pressure recording should therefore be routinely performed to identify patients with true resistant hypertension, i.e. patients who are more likely to benefit from treatment intensification.
EVALuna2:3672